A new species of Busoniomimus Maldonado-Capriles (Hemiptera: Cicadellidae: Idiocerinae) from Malaysia with a key to species of the genus - Xue, Qingquan; Zhang, Yalin (Zootaxa, 2015)
A new species, Busoniomimus umbellatus sp. nov. is described and illustrated from Malaysia. In addition the female of B. hainanensis Zhang & Li is described from China. A key is provided to males of this genus.